2011
DOI: 10.1111/j.1468-1331.2010.03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms and brain structural alterations in Fabry disease

Abstract: Against the prevailing assumption, Fabry patients, even those with marked brain structural alterations, showed only mild cognitive deficits. The high frequency of depression in FD is likely to be related to the burden of this chronic multiorganic hereditary disease, but not to the FD-typical brain structural alterations. Longitudinal studies are necessary to clear, if the mild cognitive deficits in FD might precede clinically relevant cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 36 publications
(50 reference statements)
9
74
2
2
Order By: Relevance
“…Also in line with the literature, cognitive function of the present young to middle-aged study group has been shown to be largely unimpaired. Only a small subgroup of patients with more severe WML displayed slight learning and memory deficits (Schermuly et al 2010). Additionally and also consistent with previous observations we found a high rate of depression (about 60% of the patients) in our FD cohort which was not associated with the brain structural changes and was interpreted to be mainly related to the chronic disease burden (Schermuly et al 2010).…”
Section: Introductionsupporting
confidence: 84%
“…Also in line with the literature, cognitive function of the present young to middle-aged study group has been shown to be largely unimpaired. Only a small subgroup of patients with more severe WML displayed slight learning and memory deficits (Schermuly et al 2010). Additionally and also consistent with previous observations we found a high rate of depression (about 60% of the patients) in our FD cohort which was not associated with the brain structural changes and was interpreted to be mainly related to the chronic disease burden (Schermuly et al 2010).…”
Section: Introductionsupporting
confidence: 84%
“…Likewise, lower QOL in both mental and physical domains is consistent with previous reports (Low et al 2007). Prior research found that mild deficits in executive function among 25 patients with FD compared to 20 controls were no longer significant after controlling for depression (Schermuly et al 2011). In our study, controlling for depressive symptoms, perceived stress, and QOL variables substantially attenuated the trend for lower composite cognitive scores among FD participants.…”
Section: Discussionmentioning
confidence: 97%
“…Hearing loss also can affect cognitive processing and correlates with neuropathic and vascular damage in FD (Ries et al 2007). White matter changes also are important findings; however, to date, the relation of brain abnormalities to described minor changes in cognitive function in FD is not compelling (Moore et al 2007;Muller et al 2005;Schermuly et al 2011;Fellgiebel et al 2012). Chronic distress associated with FD may have more influence on cognitive function than do pathologic alterations in the central nervous system (Segal et al 2010;Schermuly et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…17 One case of prolonged transient global amnesia has been reported in a Fabry patient. 18 Dementia, cognitive impairment, and depression occur in patients with FD 19 although additional studies are needed to establish a direct link to FD.…”
Section: Cerebral Manifestations Of Fdmentioning
confidence: 99%